Corporate social responsibility and consumption trends of working university millennial students - Rangel-Lyne, Lucirene (Universidad Autónoma de Tamaulipas, 2019)
Perceived corporate social responsibility (CSR) has been confirmed as a significant predictor of purchase behavior. Nevertheless, there are intervening variables such as “the good feelings” that involve characteristics of enjoyment, satisfaction and perceived benefit, whose effects can reinforce such behavior. In Mexico, these effects have not been sufficiently studied. Recent demographic projections, however, suggest that, in the mid-term, the national and international consumption market will be dominated by the millennial generation, especially by those who have a higher education degree and have already entered the labor market. Consequently, the objective of this article was to analyze if “the good feelings” variable increases the predictor effect of the perceived CSR on the social responsible purchase behavior. 97 university millennial students from a business school located on the southern region of Tamaulipas were surveyed. A regression model with mediation was employed to explore the mediating effects of the “good feelings” variable on the relationship between the perception of CSR and responsible consumption. The results indicated that “the good feelings” variable increases the positive and significant effect on the responsible consumption of the millennial Mexican students, due to the satisfaction, enjoyment and perceived benefit when consuming in a socially responsible way.